COMPARATIVE LAW IN DEVELOPING COURT PRACTICE IN SMALL JURISDICTIONS – MISSION POSSIBLE - Kull, Irene (Revue de droit de l'Université de Sherbrooke)

(untitled) (Revue de Droit de l’Université de Sherbrooke, 2013)
The purpose of this article is to discuss the transformative role of comparative law in the development of small nations with short legal histories, compelled to rely on borrowed ideas, concepts and regulations to create their own legal culture and reality. As a small country Estonia does not possess the necessary legal expertise or court practice in many specific areas. Here, comparative law in both of its functions – rules-based and context-based research – provides great help. The article explains how comparative law has been used in the framing of the Estonian system of civil law as well as of specific statutes. In the drafting process, a comparative law method was used to provide drafters with strategic options drawn from an array of legal systems, codes and provisions. The notion of legal transplants is widely used and explained, but in small countries, using transplants may be the only technique for building up a national legal system. The article also focuses on analysing whether the courts may use comparative law as a legal basis for developing private law. The last part of the article is dedicated to the use of comparative law in Estonian court practice, in order to illustrate that there are limits to using comparative law methods. Models of core countries may differ in their suitability because of the differences in ability to successfully absorb legal transplants or because the level of development of the society as a whole does not support the reception of transplants.